Cultural competence among pre-graduate nursing students, new graduate nurses, nurse mentors, and registered nurses: A comparative descriptive study. (February 2021) - Lin, Hui-Ling; Guo, Jong-Long; Chen, Hsiao-Jung; Liao, Li-Ling; Chang, Li-Chun
Abstract: Background: Achieving and improving cultural competence in nursing is an ongoing process, beginning in the student period and continuing through the professional career. Objectives: The present study aims to compare pre-graduate students, newly graduated nurses, registered nurses, and nurse mentors in Taiwan in terms of their respective levels of cultural competence, and to determine associated influencing factors. Design: A comparative cross-sectional study. Settings: Three universities and three hospitals (one regional hospital and two teaching hospitals) in Taiwan. Participants: A total of 756 nurses/students (103 pre-graduate nurses, 321 newly graduated nurses, 101 registered nurses, and 231 nurse mentors). Methods: The Cultural Competence Scale for Pre-Graduated Students to Licensed Professionals was used to measure the cultural competence level. One-way analysis of variance and hierarchical regression analysis were used for statistical analysis. Results: For overall cultural competence and the subscales of knowledge, awareness, and skills, the pre-graduate students scored lower than the other three groups. Experience of caring for patients from diverse cultures and countries significantly influenced the cultural competence of all four groups. Ability to speak fluent English and receiving cultural competence education during nursing education only significantly influenced the cultural competence of the pre-graduate and new graduate nurses. Current job position and primary practice setting significantly influenced the cultural competence of the registered nurses and nurse mentors. Conclusion: Pre-graduate students, newly graduated nurses, registered nurses, and nurse mentors have differing levels of cultural competence and differing influencing factors. Cultural competence education that accords with the influencing factors for each nursing position would continuously cultivate nursing staff's cultural competence.